Toward a Religious-Oriented Model of Speaking Assessment: Evidence from English Teachers in Islamic Secondary Schools - Hidayah, Siti Nurul; Shofiyuddin, Muhammad; Hasanah, Uswatun (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2025)
The domain of speaking assessment has been rigorously examined within applied linguistics. Nevertheless, many contemporary investigations predominantly emphasize elements such as delivery methodologies, linguistic standards, and the validation processes of assessment instruments, frequently overlooking the incorporation of ethical and religious considerations. This research investigates the views and practices of English teachers regarding speaking assessment in Islamic high schools in East Java, aiming to develop a framework that is more attuned to cultural needs. Using a qualitative descriptive methodology, data were collected through semi-structured interviews, classroom observations, document analysis, and stimulated recall interviews with four intentionally selected teachers. The findings reveal that educators perceive the evaluation of speaking as serving a bifunctional purpose: gauging linguistic competence (encompassing aspects such as pronunciation, fluency, and grammatical accuracy) and promoting the development of students’ moral and religious principles, including attributes like politeness, respectfulness, and integrity. Prevailing methodologies predominantly emphasize performance-oriented tasks, the implementation of analytic assessment rubrics, and the provision of corrective feedback; however, they infrequently integrate ethical standards cohesively and systematically. In light of these outcomes, the study puts forward the Religious-Values Infused Speaking Assessment (RV-ISA), which aligns CEFR descriptors with Islamic ethical principles (e.g., ṣidq, ḥilm, ḥusn al-khuluq). Conceptually, this broadens the understanding of speaking assessment to encompass value-oriented factors. This model offers teachers a clear and context-sensitive rubric, enhancing communicative competence and character education within Islamic educational settings.